To maintain vegetable agrobiodiversity for nutrition security: Insights from ethnic minorities in northern Vietnam - Nguyen, Thi Phuong; Hoang, The Ky; Pham Thi, Huong Mai; Swaans, Cornelis P.M.; Nabuuma, Deborah; Struik, C Paul; Stomph, Tjeerd-Jan (2023)
Tropentag 2023: Competing pathways for equitable food systems transformation: trade-offs and synergies in Humboldt-Universität zu Berlin, Germany, September 2023. Poster presentation titled “To maintain vegetable agrobiodiversity for nutrition security: Insights from ethnic minorities in northern Vietnam”.